Affective neuroscience theory and attitudes towards artificial intelligence - Christian Montag (413788) (2024)
Artificial intelligence represents a key technology being inbuilt into evermore products. Research investigating attitudes towards artificial intelligence surprisingly is still scarce, although it becomes apparent that artificial intelligence will shape societies around the globe. To better understand individual differences in attitudes towards artificial intelligence, the present study investigated in n = 351 participants associations between the Affective Neuroscience Personality Scales (ANPS) and the Attitudes towards Artificial Intelligence framework (ATAI). It could be observed that in particular higher levels of SADNESS were associated with higher negative attitudes towards AI (fearing AI). The findings are discussed in this work from an evolutionary perspective because primary emotional systems—according to Affective Neuroscience Theory—represent tools for survival, which have been homologously conserved across mammalian species including homo sapiens. Other Information Published in: AI & SOCIETY License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00146-023-01841-8